Flexible working: effects on women’s work-life balance, lifestyle and health - Abdullah, Nor Hazana; Abdul Kadir, Adibah; Abdul Kadir, Zulida; Sabar, Sarinah (American Scientific Publishers, 2018)
Flexible working arrangement is a future work trends in response to growing concerns for evolving workforce demographics and retaining women in workforce. However, there are limited studies that actually compare the perception of women who worked conventional hours and flexible hours on WLB, lifestyle and health. Thus, this study aimed to examine perception towards WLB, lifestyle and health between women who worked in conventional working hour and those who worked flexible working hour. This study used survey data from 177 respondents (98 flexible working women; 79 conventional working women) from four companies which offer both types of working arrangements. Despite consistent empirical support on the positive effect of flexible working on leisure and health, t-test result indicates that only WLB balance is affected by flexible working hour. Contrary to previous understanding on WLB, women working in conventional working time perceived high level of WLB compared to those who worked using flexible working time. This finding necessitates further replication with more data. It also implies that WLB is a complex phenomenon which needs to be studied further.